Strategies of Indefiniteness Marking in Central Sicilian—Evidence from the Dialect of Delia - Vincenzo Nicolò Di Caro (Languages, 2023)
This paper is meant as a contribution to the research project on variation and optionality in the determiner system in Italo-Romance, with novel data from the Sicilian dialect of Delia. The study is based on fieldwork interviews and the construction of a small corpus of 850 observations by 24 native speakers of Deliano (mean age: 36.37; age range: 19–72). The participants were asked to (i) describe in Deliano a 3 min videotape of an Italian speaking woman during her shopping session at a supermarket and (ii) talk about their own shopping routines in Deliano. These activities were designed mainly to detect the following strategies to express indefiniteness: (i) ART, i.e., a definite article with an indefinite interpretation; (ii) ZERO, a zero determiner for bare nouns; (iii) DI+ART, the so-called “partitive article”; (iv) pseudo-partitives such as ‘a bit of’; (v) the grammaticalised cardinal ‘two’; and (vi) the grammaticalised cardinal ‘four’. The data confirm (i) the preference for ZERO in negative episodic sentences in the past; (ii) the general lack of bare DI and DI+ART, and of certo ‘certain’ used as an indefinite; (iii) the use of different specialised forms of pseudo-partitive ‘a bit of’ in older speakers of Deliano; (iv) the neutralisation of this pseudo-partitive specialisation and the consequent emergence of some true optionality in younger speakers.